2021
DOI: 10.1007/s11306-021-01795-2
|View full text |Cite
|
Sign up to set email alerts
|

Time-course analysis of Streptococcus sanguinis after manganese depletion reveals changes in glycolytic and nucleic acid metabolites

Abstract: Introduction Manganese is important for the endocarditis pathogen Streptococcus sanguinis. Little is known about why manganese is required for virulence or how it impacts the metabolome of streptococci. Objectives We applied untargeted metabolomics to cells and media to understand temporal changes resulting from manganese depletion. Methods EDTA was added to a S. sanguinis manganese-transporter mutant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…The most highly enriched pathway for the ΔssaACB mutant was the "Porphyrin/ Chlorophyll" pathway but upon examination, these genes encode the cobalamin biosynthetic enzymes (Table S2), which were also significantly downregulated in our recent study of manganese depletion . Many of the pathways highlighted by this analysis, such as carbon metabolism and amino acid metabolism, were also affected by manganese reduction in our recent transcriptomic and metabolomic studies Puccio, Misra, et al, 2021).…”
Section: Rna-seq Analysis Of Fermentor-grown Sk36 Wt and δSsaacb Cell...mentioning
confidence: 58%
See 3 more Smart Citations
“…The most highly enriched pathway for the ΔssaACB mutant was the "Porphyrin/ Chlorophyll" pathway but upon examination, these genes encode the cobalamin biosynthetic enzymes (Table S2), which were also significantly downregulated in our recent study of manganese depletion . Many of the pathways highlighted by this analysis, such as carbon metabolism and amino acid metabolism, were also affected by manganese reduction in our recent transcriptomic and metabolomic studies Puccio, Misra, et al, 2021).…”
Section: Rna-seq Analysis Of Fermentor-grown Sk36 Wt and δSsaacb Cell...mentioning
confidence: 58%
“…We recently reported that manganese depletion led to induction of carbon catabolite repression (CCR) in S. sanguinis (Puccio et al., 2020; Puccio, Misra, et al., 2021). Given that both addition of acid and EDTA (Puccio, Misra, et al., 2021) led to reduced manganese levels in the fermentor (Figure 4), we hypothesize that the impact on glycolysis is similar to what we observed in our previous study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the chain length of ∆ gloA2 SM / fruI was considerably shorter than that of the wild type, a result echoed what was reported previously in ∆ fruI SM background [ 35 ]. Regarding the phenotype of ∆ gloA2 SM when growing on BMGS and BHI, it has been demonstrated that sucrose catabolism by S. mutans often leads to release of free fructose; BHI medium contains a small amount of fructose contaminant [ 38 , 39 ].
Figure 6.
…”
Section: Resultsmentioning
confidence: 99%